2018
DOI: 10.1161/circresaha.117.312472
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Production and Diurnal Regulation of Vascular RvD n-3 DPA Increase Systemic Inflammation and Cardiovascular Disease

Abstract: These results demonstrate that peripheral blood RvD are diurnally regulated in humans, and dysregulation in the production of these mediators may lead to cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 25 publications
3
57
0
Order By: Relevance
“…The D-series resolvin RvD1 led to smaller necrotic cores, enhanced rates of lesional efferocytosis, and thicker collagen caps when administered to high-fat-fed Ldlr -/mice (14). Similarly, administration of RvD5 n-3 DPA (derived from n-3 docosapentaenoic acid) to high-fat-fed Apoe -/mice decreased atherosclerotic lesion size and reduced leukocyte and platelet activation (50). Treatment of Apoe -/mice with RvD2 and MaR1 also promoted plaque stability by decreasing lesional macrophage numbers, halting expansion of necrotic cores, and thickening collagen caps (15).…”
Section: Imbalance Of Inflammatory and Resolving Mediators Drives Athmentioning
confidence: 97%
See 1 more Smart Citation
“…The D-series resolvin RvD1 led to smaller necrotic cores, enhanced rates of lesional efferocytosis, and thicker collagen caps when administered to high-fat-fed Ldlr -/mice (14). Similarly, administration of RvD5 n-3 DPA (derived from n-3 docosapentaenoic acid) to high-fat-fed Apoe -/mice decreased atherosclerotic lesion size and reduced leukocyte and platelet activation (50). Treatment of Apoe -/mice with RvD2 and MaR1 also promoted plaque stability by decreasing lesional macrophage numbers, halting expansion of necrotic cores, and thickening collagen caps (15).…”
Section: Imbalance Of Inflammatory and Resolving Mediators Drives Athmentioning
confidence: 97%
“…Using lipid mediator profiling of healthy volunteers, Colas et al demonstrated that plasma concentrations of the DPA-derived D-series resolvins (RvD n-3 DPA ) are diurnally regulated. Further, the pattern of regulation was significantly impaired in patients with cardiovascular disease (50). These patients were also found to have increased leukocyte activation and higher levels of circulating platelet-leukocyte aggregates, which have been shown to be a marker of inflammation (50).…”
Section: R E V I E W S E R I E S : L I P I D M E D I At O R S O F D Imentioning
confidence: 99%
“…In this context, recent studies in healthy volunteers found that supplementation with n‐3 DPA increased plasma RvD5 n‐3 DPA concentrations (Markworth et al ., ). Using a lipid mediator profiling approach, we found that in humans systemic concentrations of RvD n‐3 DPA diurnally regulated and their concentrations correlate with markers of both platelet and leukocyte activation including CD11b and CD62P (Colas et al ., ).…”
Section: The Identification and Structure Elucidation Of Novel Immunomentioning
confidence: 97%
“…This relationship was coupled with a trend towards an increase in the concentrations of pro-inflammatory mediators in those with more severe disease (Figure 1B). Assessment of the resolution index, that is the ratio between the concentrations of pro-resolving mediators and pro-inflammatory eicosanoids, (16) also demonstrate a reduction in the resolution index, indicative of increased inflammation, in patients with the more severe disease (Figure 1C).…”
Section: Resultsmentioning
confidence: 91%
“…Using targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based profiling of CSF we identified mediators from all four major bioactive metabolomes, including the AA-derived lipoxin (LX)s, leukotriene (LT)s and prostaglandin (PG)s and the n-3 DPA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)-derived resolvin (Rv)s (Supplemental Table 2). In order to gain insights into the relationship between CSF lipid mediator concentrations and disease severity we first grouped the mediators by biological function assessing the differences between pro-resolving mediators (lipoxins, resolvins, protectins and maresins) and pro-inflammatory mediators (leukotrienes, prostaglandins and thromboxane) in patients with moderate or severe disease (MRC grades 2 and 3) when compared with those with mild disease (MRC grade 1)(16)(Figure 1A, Supplemental Table 2). Results of this analysis demonstrated that with increasing disease severity there was a decrease in overall pro-resolving lipid mediator concentrations in the CSF of patients with TBM (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%